PENERAPAN METODE PEMBELAJARAN PREVIEW QUESTION READ STATE AND TEST (PQRST) UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA PADA POKOK BAHASAN STRUKTUR ATOM DI KELAS X IPA SMA MUHAMMADIYAH 1 PEKANBARU - Thaib, Armiyus Thaib; ', Mariana; ', Miharty (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract:This research aims to increase student achievement on the subject Atomic Structure in class X IPA SMA Muhammadiyah 1 Pekanbaru. This research is a kind of experiment research with pretest-posttest design. The research was conducted in SMA Muhammadiyah 1 Pekanbaru. The samples of this research were the students of class X IPA 3 as the experimental class and students of class X IPA 4 as the control class. Experimental class is a class that is applied the use of Metode PQRST while the control class was not. Data analysis technique used is the t-test. Based on analysis of data obtained tarithmetic> ttable is 2,8284 > 1,67, means that the use of metode PQRST can improve student achievement on the subject of atomic structure class X IPA SMA Muhammadiyah 1 Pekanbaru, increase learning of 11,2%. Keywords : Learning Achievement, Method PQRST, and Atomic Structure